HUBUNGAN ANTARA HARGA DIRI DENGAN FEAR OF MISSING OUT PADA REMAJA SMA NEGERI 1 TONDANO PENGGUNA INSTAGRAM - Polii, Gaudia M.; Deetje Solang ,; Sinta Kaunang, (PSIKOPEDIA, 2024)
This study aims to determine the relationship between self-esteem and fear of missing out among teenagers at SMA Negeri 1 Tondano who use Instagram, analyze the differences in levels between self-esteem and fear of missing out in male and female teenagers, and analyze the level of the fear of missing out variable. seen from the age factor, and analyzing the level of the fear of missing out variable seen from the duration factor of using Instagram in a day. This research is quantitative research with a correlational approach. The subjects in this study numbered 100 out of a total population of 139 Class XII SMA students. The sampling technique in this research used a non-probability sampling method. Based on the results of the data analysis carried out, it shows that there is a significant relationship of 0.003 with a Pearson correlation of -0.290, meaning that the lower self-esteem, the higher the fear of missing out, and vice versa. Meanwhile, the t-test for equality of means has sig values ​​of 0.191 and 0.187 (X) and 0.357 and 0.332 (Y) (p>0.05) which means that there is no difference between male and female respondents in the price variable. self (X) and fear of missing out (Y), while for the age category of the fear of missing out variable it is concluded that age is one of the factors that can influence the level of fear of missing out, for the level of the fear of missing out variable it is seen from the duration factor Using Instagram in a day can be seen that there are differences between each time period.